Expediente e apresentação da edição: v. 14, n. 2, jun./jul. 2023 - Dias, Chiara Maria Seidel Luciano; Brugnera, Elisângela Dias; Siebiger, Ralf Hermes (Eventos Pedagógicos, 2023)
Expediente e apresentação da edição - v. 14, n. 2, jun./jul. 2023